2020
DOI: 10.22146/mot.59226
|View full text |Cite
|
Sign up to set email alerts
|

Loading and Release Profile Assay of Carbonated Hydroxyapatite Incorporated with Propolis as Bone Graft Material

Abstract: Periodontitis can lead to the destruction of the alveolar bone. The loss of the alveolar bone can be treated using carbonated hydroxyapatite (CHA) as a bone graft material. However, CHA is an alloplastic graft whose primary function is to act as a scaffold, but it is unable to stimulate the process of bone regeneration. Carbonated hydroxyapatite is an avascular synthetic material, which will increase the risk of bacterial adhesion on site that can lead to unsuccessful periodontal therapy. The incorporation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…To acquire 10% propolis-CHA, the 10mg CHA was then immersed in 1ml of 10% propolis solution for 24 hours at room temperature. 11 The experimental animals that were used were six male rabbits (Oryctolagus cuniculus) aged 5-8 months, weight 1500-2000g and induced with periodontitis. Periodontitis induction on the rabbits was performed by the ligation technique and injection of lipopolysaccharide (LPS) from Porphyromonas gingivalis ATCC 33277 from Thermo Scientific, USA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To acquire 10% propolis-CHA, the 10mg CHA was then immersed in 1ml of 10% propolis solution for 24 hours at room temperature. 11 The experimental animals that were used were six male rabbits (Oryctolagus cuniculus) aged 5-8 months, weight 1500-2000g and induced with periodontitis. Periodontitis induction on the rabbits was performed by the ligation technique and injection of lipopolysaccharide (LPS) from Porphyromonas gingivalis ATCC 33277 from Thermo Scientific, USA.…”
Section: Methodsmentioning
confidence: 99%
“…9 An in vivo study showed that 10% propolis gel could stimulate the healing process of gingivitis in experimental animals by reducing the number of polymorphonuclear (PMN) cells, increasing the number of fibroblasts, and stimulating the formation of angiogenesis. 10 A previous study showed that CHA immersed in 10% propolis solution had an excellent mechanical and chemical bond between the two materials, 11 and this new material showed excellent capability in stimulating fibroblast cell lines. 12 Devitaningtyas et al 13 proved the inhibition properties of CHA-10% propolis against Porphyromonas gingivalis.…”
Section: Introductionmentioning
confidence: 97%